1885-86 Va. Acts 275, ch. 258, § 10 - (:unkn) unknown (My University, 1885)
Any person who shall willfully destroy, injure or remove any tombstone or monument placed in the said cemetery . . . or shall shoot of or discharge any gun, pistol or other firearm within the said enclosure, shall be guilty of a misdemeanor, and shall, upon conviction, be fined not less than five dollars. . .
Keywords: DISCHARGE